The Power of Evaluation: Transforming Teaching and Learning - Chamisah (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Evaluation is a fundamental component of the educational process, essential for measuring and improving student learning. This study explores the multifaceted role of evaluation, emphasizing formative and summative assessments, technological integration, and reflective practices. Formative assessments offer real-time feedback, allowing educators to adapt instruction and address learning gaps, while summative assessments provide a comprehensive overview of student achievements at the end of instructional periods. The integration of technology into evaluation practices enhances data collection and analysis, supports personalized learning experiences, and introduces diverse assessment methods. Reflective practices foster continuous improvement by helping students and educators set goals, develop strategies, and refine performance. Ensuring fairness and inclusivity in evaluations promotes equity and supports diverse learner needs. Utilizing a library research design, this study systematically collects, evaluates, and synthesizes academic sources to provide a comprehensive understanding of these evaluation components. The findings highlight the need for a balanced approach that combines formative and summative assessments, leverages technology, and incorporates reflective practices to improve student outcomes and overall educational quality.